Learning Systems in the Republic of Korea: Lessons From the School - Raveendran, Ashita (THE PRIMARY TEACHER, 2022)
With technological change and the hastening pace of growth, the way of living is being reshaped, which necessitates reflective changes to occur in the education system of every country. Yet, we stumble in nurturing our students with the requisite skills to steer them through the economy of the future. This paper looks into the education system of the Republic of Korea by providing glimpses from the school visit conducted as a part of the Global Capacity-Building Workshop on Global Citizenship Education (GCED) organised by the Asia-Pacific Centre of Education for International Understanding (APCEIU), Korea. The visit, apart from sharing the culture of India with the Korean students, helped in gathering insights into the education system of the Republic of Korea. The classroom observation and visit to their learning labs allowed for gaining information about how skills and competencies are given more importance even at the elementary level of education in the Republic of Korea.